Double Whammy: Why the Underrepresentation of Women among Workplace and Political Decision Makers Matters in Pandemic Times. Issue 4 (December 2020) - Brooks, Deborah Jordan; Saad, Lydia
Abstract: In this article, we explore whether women's underrepresentation among political and workplace decision makers may subject female citizens and employees to COVID-19-related decisions that are at odds with their preferences. We find that women overall, as well as female political party members, workers, and workplace leaders in particular, share a distinctively female perspective that more heavily emphasizes caution with respect to COVID-19 compared with men. Given the limited representation of women leaders across most industries and in politics, COVID-19 regulations are thus likely to be less cautious than would be the case if there were an equitable representation of women across leadership roles. We argue that female employees, in particular, face a representational "double whammy" for COVID-19: gender imbalances in workplace leadership create inequities that are compounded—rather than redressed—by unequal political representation. We conclude by addressing how this dynamic may enhance the movement of women away from Republican candidates moving forward.